Assessment of the incidence rate of end-stage renal disease in patients with and without diabetes in Poland - Waldemar Wierzba (Annals of Agricultural and Environmental Medicine, 2018)
Introduction Several studies have suggested, that diabetes is very important factor of the risk of the chronic a renal disease. The paper aims to present a retrospective analysis of incidence of end-stage renal disease in subgroups of patients with and without diabetes in Poland.